TINGKAT EFISIENSI PENGELUARAN PEMERINTAH DAERAH DI PULAU JAWA - Zuhairan Y Yunan (Signifikan: Jurnal Ilmu Ekonomi, 2014)
The objective of this research is to analyze the local government spending for education and health sector for all provices in the Java Island. The data used in this research is local government spending for education and health sector. The data are Life Expectancy Rate, Literacy Rate, and Average of School Duration. A method of analysis used to measure performance through health and education spending with DEAP software version 2.1. The result showed that local government spending for education and health sector has not been efficient. Only Yogyakarta Province showing that local government spending is already efficient, also in the term of output (Literacy Rate and Average of School Duration). Local government spending for health sector has not been efficient. Only Yogyakarta Province showing that local government spending is already efficient, also in the term of output (Life Expectancy Rate)DOI: 10.15408/sjie.v3i1.2053